Comfortable and Peaceful at Budi Dharma ElderlyHome Service - Kuntjorowati, Elly (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research aimed to describe social services provided by Budi Dharma elderly home care. There were three persons acted as main informants and they worked as elderly home care administrators and social workers, and five persons living in the elderly home care acted as supporting informants. The selection of informants is conducted purposively in accordance with the needs of the data relevant to this research. The research took place at Budi Dharma Elderly Home Care which is located at Giwangan, Umbulharjo Yogyakarta. Data collection carried out through in-depth interviews, and through that of observation and documentary analysis of secondary data related to the research topic. Data gained were analyzed descriptively and qualitatively by using graphic into the aspects of the research that has been determined and presented in percentage, in order to obtain information that describes the work of the social services. The results showed that the elderly feel happy, comfortable and peaceful for Elderly Home Care functions properly in accordance with the standardization of an elderly home care operation. Budi Dharma elderly home care has an organizational structure, infrastructure, administration, financing, and network development. In addition, it has also Elderly Home Care standard operating procedures (SOP) and has a fixed schedule of activities.